2008
DOI: 10.1097/wnr.0b013e32830fe4b8
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin 3-O-glucopyranoside protects and rescues SH-SY5Y cells against amyloid-beta peptide-induced toxicity

Abstract: The amyloid-beta (A beta) peptide (1-42) aggregation into oligomeric and fibrillar species affects neuronal viability, having a causal role in the development of Alzheimer's disease. Among dietary anthocyanins, cyanidin 3-O-glucoside (Cy-3G) and its metabolites, such as protocatechuic acid (PA), have gained attention as potential neuroprotective agents. In this in-vitro study, we demonstrated that Cy-3G, but not PA, can inhibit A beta1-42 spontaneous aggregation using thioflavin T fluorescence assay and transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 21 publications
0
30
1
Order By: Relevance
“…In these cells, the levels of GSH and the activity of catalase increase, while GPx activity remains unchanged, suggesting that PCA acts mainly as antioxidant [204]. This hypothesis has been confirmed by Tarozzi et al [205] that have demonstrated the ability of cyanidin and PCA, but not of C3G, to inhibit mitochondrial function loss and DNA fragmentation. The potential protective effects of compounds generated during in vivo metabolism of ACNs has been the topic of comparative studies on the effects of different compounds in the human neuroblastoma cell line SH-SY5Y.…”
Section: Anti-apoptotic Effects Of Pcamentioning
confidence: 72%
See 1 more Smart Citation
“…In these cells, the levels of GSH and the activity of catalase increase, while GPx activity remains unchanged, suggesting that PCA acts mainly as antioxidant [204]. This hypothesis has been confirmed by Tarozzi et al [205] that have demonstrated the ability of cyanidin and PCA, but not of C3G, to inhibit mitochondrial function loss and DNA fragmentation. The potential protective effects of compounds generated during in vivo metabolism of ACNs has been the topic of comparative studies on the effects of different compounds in the human neuroblastoma cell line SH-SY5Y.…”
Section: Anti-apoptotic Effects Of Pcamentioning
confidence: 72%
“…neurons by interfering with the increase of [Ca(2+)], and by inhibiting glutamate release, generation of ROS and caspase-3 activity [208]. However, C3G, but not PCA, might protect and rescue the neuronal cells from toxicity induced by A , by inhibiting its spontaneous aggregation in human neuronal SH-SY5Y cells [205]. A recent study has been aimed at investigating the protective effects exerted by PCA against apoptosis induced by oxidized lipids in intestinal Caco-2 cells [100].…”
Section: Anti-apoptotic Effects Of Pcamentioning
confidence: 97%
“…Cyanidin-3-O-glucopyranoside (Cy-3G), an anthocyanin that abundant in colorful vegetables and fruits, has recently been identified as neuroprotective phytochemicals. It decreases Aβ peptide-mediated cytotoxicity in SH-SY5Y neurocytes [34]. Cy-3G also could reduce cerebral ischemia and ageing-related neuronal deficits in animal model [35].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was also shown to be a cognitive improvement in older humans (Krikorian et al, 2010). In line with this view, studies with the Cyanidin-3-O-glucopyranoside (Cy-3G), an isolated Antho and abundant in colorful vegetables and fruits, has recently been identified as potent neuroprotective phytochemical since this compound protects against Aβ peptide-mediated cytotoxicity in SH-SY5Y neurocytes (Tarozzi et al, 2008(Tarozzi et al, , 2007(Tarozzi et al, , 2010 and also can reduce cerebral ischemia damage and age-related neuronal deficits (Shin et al, 2006).…”
Section: Groupmentioning
confidence: 89%